Nuss procedure: Technical modifications to ease bending of the support bar and lateral stabilizer placement - Osman Zeki Karakus; Oktay Ulusoy; Gulce Hakguder; Oguz Ates; Cimen Olguner; Mustafa Olguner; Feza Mirac Akgur (Annals of Thoracic Medicine, 2016)
Background: Modifications defined to ease bending of the support bar and lateral stabilizer placement during minimal invasive repair of pectus excavatum (MIRPE) have not been reported. We herein report our experience with MIRPE including several technical modifications. Methods: A total of 87 patients who underwent MIRPE were evaluated retrospectively. Technical modifications are (1) a template drawn preoperatively according to the anthropometric measurements, (2) more laterally placed thoracal incisions, (3) single existing incision for multiple support bars, (4) to secure lateral stabilizers to support bar in inverted position. Results: The mean patient age was 11.2 ± 3.8 years. The mean operating time was 63.7 ± 18.7 min. The mean Haller index was 5.4 ± 2.1. Eight patients necessitated two support bars. The support bars were removed in 69 patients after the completion of treatment. Support bars were left in place 26.8 ± 4.3 months. Final chest contours of the 56 patients were evaluated as 12 months passed after support bar removal and excellent repair results were determined in 84.2%. Conclusion: Preoperative bending of the support bar according to anthropometric measurements and fixation of the lateral stabilizers to the support bar in inverted position facilitates bar shaping and lateral stabilizer placement.